‘A hundred altar cards in parchment’: A 'sine notis' unknown work from Jorge Coci's workshop in Zaragoza in the National Historical Archive - Carvajal González, Helena (Revista General de Información y Documentación, 2019)
This article provides information of the existence, in the Inquisition Section of the Archivo Histórico Nacional, of a fragment of an altar card or tabella secretarum printed on parchment in Jorge Coci's workshop in Zaragoza. The importance of this liturgical print, reused as a binding for a grimoire requisitioned in an inquisitorial process, is explained, as it is one of the few testimonies preserved in the Iberian Peninsula of pre-tridentine altar cards of which the above-mentioned Zaragozan workshop made extensive editions of which, to the present day, no material evidence was found.
Keywords: Altar cards; Tabellae secretarum; Zaragoza’s printing press; Jorge Coci; Liturgical prints; 16th Century